2006
DOI: 10.1002/acp.1199
|View full text |Cite
|
Sign up to set email alerts
|

The impact of background musical tempo and timbre congruity upon ad content recall and affective response

Abstract: This study investigated whether the tempo and timbre of background music influenced responses to radio ads. In Experiment 1 (in addition to a no-music control condition), slow-or fast-tempo background music was superimposed over the same ad. The slow-tempo music treatment produced significantly higher levels of ad content recall compared to the fast-tempo music treatment. Musical presence (slow-and fast-tempo treatments combined vs. no-music) significantly reduced levels of ad content recall. In Experiment 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
2
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 33 publications
(42 reference statements)
4
64
2
9
Order By: Relevance
“…For example, various studies have suggested that both verbal (e.g. Kellaris, Cox, and Cox 1993;North et al 2004;Oakes and North 2006) and visual (e.g. Stewart, Farmer, and Stannard 1990) advertising content recall is likely to be significantly higher with stimuli that are congruous with the advertisement.…”
Section: Journal Of Marketing Communications 185mentioning
confidence: 97%
See 1 more Smart Citation
“…For example, various studies have suggested that both verbal (e.g. Kellaris, Cox, and Cox 1993;North et al 2004;Oakes and North 2006) and visual (e.g. Stewart, Farmer, and Stannard 1990) advertising content recall is likely to be significantly higher with stimuli that are congruous with the advertisement.…”
Section: Journal Of Marketing Communications 185mentioning
confidence: 97%
“…Indeed, previous research (Oakes and North 2006) has suggested that participants may only seek to evaluate cognitively the purpose of incongruous advertising stimuli when the advertised good or service has personal relevance for them. Consequently, the current study used an advertisement for a service with which all participants had experience (a fictitious university targeting students for undergraduate and postgraduate courses).…”
mentioning
confidence: 99%
“…Furthermore, Oakes et al used two experiments to show how background music that displays a different timbre and tempo contributes to ad content recall and response [10]. The study gave a common description of what tempo is declaring "musical tempo is the speed at which a musical passage progresses".…”
Section: Resultsmentioning
confidence: 99%
“…The shopping and service industries have studied background music's broad effects on consumer behaviour, including time spent on premises, amount spent, and improved attitudes -in both retail outlets (Alpert & Alpert, 1990;Oakes, 2000;Chebat et al, 2001) and restaurants (Caldwell & Hibbert, 2002). Outside of the store, music influences consumers' affective response to advertisements and their ability to recall its content (Oakes & North, 2006). When strong emotions accompany an event, it becomes easier to remember (Levine & Burgess, 1997;Dolan, 2002).…”
Section: Potential Applicationsmentioning
confidence: 99%